1999
DOI: 10.1089/088922299310340
|View full text |Cite
|
Sign up to set email alerts
|

Normal Telomere Lengths in Naive and Memory CD4+ T Cells in HIV Type 1 Infection: A Mathematical Interpretation

Abstract: To study CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
6
16
0
Order By: Relevance
“…In this data, the increase in average cellular turnover rates caused by SIV infection is typically Ͻ2-fold. This level of increase in cellular turnover is in good agreement with telomere data showing little effect of HIV infection on the average telomere length in naive and memory CD4 ϩ T cells (17,48), and with TCR rearrangement excision circle data showing a decrease in the TCR rearrangement excision circles per naive T cell in response to a small increase in the division rate (49).…”
Section: Discussionsupporting
confidence: 89%
“…In this data, the increase in average cellular turnover rates caused by SIV infection is typically Ͻ2-fold. This level of increase in cellular turnover is in good agreement with telomere data showing little effect of HIV infection on the average telomere length in naive and memory CD4 ϩ T cells (17,48), and with TCR rearrangement excision circle data showing a decrease in the TCR rearrangement excision circles per naive T cell in response to a small increase in the division rate (49).…”
Section: Discussionsupporting
confidence: 89%
“…First, by determining the fraction of dividing cells through expression of the nuclear antigen Ki67 (12), it was shown that T-cell proliferation rate is increased maximally twofold to threefold in the CD4 + population, and sixfold to sevenfold in the CD8 population (13-16). This limited increase in the division rate is consistent with results of studies that measured the replicative history of T cells by the average telomere lengths (17,18). The second technique, using deuterated glucose to label DNA in vivo, showed that the turnover of CD4 + and CD8 + T cells in HIV-infected patients is about three times higher than that of uninfected individuals (19).…”
supporting
confidence: 75%
“…As we have discussed, new experimental evidence on T cell production numbers in normal controls and HIV-infected patients suggests that CD4+ T cell production is about two-to threefold increased with HIV-1 infection and is on the order of 109 cells per day ( Table I). Studies that provided a mathematical interpretation of telomere length dynamics in CD45RA+ and CD45R0+ CD4+ cells demonstrated that telomere shortening rates comparable to uninfected controls are compatible with a small increase in production of CD4+ T cells (Wolthers et al, 1996(Wolthers et al, , 1998. Therefore, the data suggest that there is a modest increase in the amount of proliferation of T cells in HIV-1-infected individuals.…”
Section: What Is the Cause Of Cd4+ T Cell Depletion In Hiv-1 Infementioning
confidence: 80%